ANALISIS EFISIENSI INFRASTRUKTUR TRANSPORTASI LIGHT RAIL TRANSIT (LRT) DALAM MENGATASI KEMACETAN KOTA PALEMBANG - Hidayah, Nuril; Masduqie, Muhammad Hamdan Ali (Journal of Economics and Policy Studies (JEPS), 2022)
Palembang city congestion occurs as a result of road capacity in Palembang City which is not balanced with the number of vehicles. In addition, flooding at several points also has an impact on traffic jams. As the population increases, city congestion is expected to get worse. Therefore, the government is looking for ways to reduce traffic congestion by developing a public transportation system that aims to shift the use of private cars to public transportation. Transportation is a very important need in supporting people's daily lives. In addition to the mission of reducing the number of road congestion, the government is also working on a level of efficiency in the implementation of the transportation so that the public's attractiveness in switching to public transportation becomes greater so that readers can understand In terms of accessibility, what are the priority variables in implementing light rail transit and how much efficient implementation of light rail transit to reduce congestion in the city of Palembang This journal uses a research approach in the descriptive qualitative category, data collection techniques through observation or observation, but the observations made by researchers are included in the indirect category. This is because these observations through the media of articles, news and journals related to the implementation of land use in Indonesia and using secondary data sources LRT is a means in the form of infrastructure built by the government in collaboration especially with parties from the regional government to achieve two goals. The main goal is to reduce the number of congestion that exists on the basis of high efficiency and both goals are considered to have been realized in the implementation of the infrastructure. Indeed not all cities have these infrastructure facilities, state leaders are trying to evenly distribute assification in all existing cities, currently the areas that have been equipped with light rail are in the cities of Palembang and Jakarta, as well as other areas that fall into the category or term. Jabodebek. The priority variables in the accessibility point of the transportation implementation are the availability of wide access roads in or out of the station, the existence of parking facilities that are endeavored to be adequate to make the public or vehicle users feel comfortable and safe, the proximity of the station to the center of activity within the scope of commercial facilities such as offices, with shopping centers such as malls, close to housing or community settlements (citizens), the ease of access to public transportation to go to the station, close to the main road or highway, one of the goals of the asification is expected to be a medium for parse the number of traffic jams on the existing roads. The community considers the asification to be in the efficient category because the tariffs charged are in the cheap (economical) category, but it is different from the government as the subject of the assification, they consider that for light rail transit asiffication requires a large amount of funds, of course it does not require With few funds, tens of trillions of funds have been disbursed for the assification of the LRT, which was contributed by the government itself, companies on behalf of state-owned railways and received injections or injections of funds from investors and loan funds, it can be concluded that the implementation of this infrastructure is considered quite efficient and can make the congestion rate shrink slowly